Hubungan Persepsi Metode Fami bisyauqin terhadap Kecerdasan Emosional Hafiz di Pondok Pesantren Putri Al-Baqoroh Lirboyo - Indah Halimatus Sa’diyah; Moh. Turmudi (Indonesian Journal of Humanities and Social Sciences, 2022)
The learning technique for remembering the Qur'an is exceptionally pivotal and is one of the achievement factors in retaining the Qur'an. The low familiarity with people rehashing repetition remembrance and adding retention to the educator is the fundamental issue in Al-Qur'an foundations or Islamic live-in schools. This review intends to decide the connection between the impression of the fami bisyauqin technique on the capacity to appreciate individuals on a profound level of hafiz at the Al-Baqoroh Lirboyo Islamic Live-in School. This study utilizes a quantitative methodology that uses the Kendall tau equation examination. The area of this exploration is the Al-Baqoroh Lirboyo Islamic All-inclusive School. Information assortment methods The investigation utilized a survey with an example of 123 hafizes from 1382 of the number of inhabitants in understudies examined. The consequences of the review indicated that the degree of view of the fami bisyauqin technique on hafiz's capacity to understand individuals on a deeper level was undeniable. In any case, the worth on the speculation test between the ability to understand people on a deeper level and the apparent relationship of the fami bisyauqin technique brought about worth of 0.103 with a meaning of 0.054, and that truly intends that there is no connection between the view of the bisyauqin fami strategy and the emotional intelligence hafiz. This is because understudies follow the ustadzah strategy.